Laforin, a dual specificity protein phosphatase involved in Lafora disease, is phosphorylated at Ser25 by AMP-activated protein kinase - Romá-Mateo, Carlos (2011)
Lafora progressive myoclonus epilepsy (Lafora disease; LD) is a fatal autosomal recessive neurodegenerative disorder caused by loss-of-function mutations in either the EPM2A gene, encoding the dual specificity phosphatase laforin, or the EPM2B gene, encoding the E3-ubiquitin ligase malin. Previously, we and others showed that laforin and malin form a functional complex that regulates multiple aspects of glycogen metabolism, and that the interaction between laforin and malin is enhanced by conditions activating AMP-activated protein kinase (AMPK). Here, we demonstrate that laforin is a phosphoprotein, as indicated by two-dimensional electrophoresis, and we identify Ser25 as the residue involved in this modification. We also show that Ser25 is phosphorylated both in vitro and in vivo by AMPK. Lastly, we demonstrate that this residue plays a critical role for both the phosphatase activity and the ability of laforin to interact with itself and with previously established binding partners. Our data suggest that phosphorylation of laforin-Ser25 by AMPK provides a mechanism to modulate the interaction between laforin and malin. Regulation of this complex is necessary to maintain normal glycogen metabolism. Importantly, Ser25 is mutated in some Lafora disease patients (S25P), and our results begin to elucidate the mechanism of disease in these patients.